Sensory acceptance drivers of pre-fermentation dehydration and submerged cap red wines produced from Vitis labrusca hybrid grapes - Castilhos, Mauricio B. M. de [UNESP]; Garcia Maia, Joao Dimas; Gomez-Alonso, Sergio; Del Bianchi, Vanildo Luiz [UNESP]; Hermosin-Gutierrez, Isidro (Elsevier B.V., 2016)
The pre-fermentation dehydration (PD) and submerged cap (SC) treatments were evaluated as alternative winemaking for Brazilian red table wines produced from Vitis labrusca cultivar Bordo and hybrid cultivars Isabel, BRS Carmem and BRS Violeta. The influence of these treatments on the wine chemical profile and their contribution to sensory acceptance drivers has been evaluated. The pre-drying process tended to increase the total phenolic content (up to 1677 mg L-1 of gallic acid) and the dry extract of the wines (up to 47.89 g L-1), considering them as full-bodied and more attractive to consumers. The univariate approach revealed slight influence of the alternative winemaking treatments on wine composition and sensory acceptance. However, PCA was successfully applied and showed that the positive effects of the pre-drying treatment on Bordo and BRS Carmem body acceptance, which was driven by acidity, dry extract and phenolic compounds. The results also suggested that submerged cap positively influenced almost all the sensory attributes of Isabel and BRS Violeta wines, which were driven by acidity and color features. The management of these winemaking processes needs to be assessed, since provides an intense acceptance for key sensory attributes considered as acceptance drivers for a target group of consumers. (c) 2016 Elsevier Ltd. All rights reserved.
Keywords: Red wine; Drying; Submerged cap; Hybrid grapes; Sensory analysis; Acceptance drivers